SPATIAL DEVELOPMENT OF THE RUSSIAN TERRITORY IS REQUIREMENT OF TIME - N. N. Musinova (Вестник университета)
In the last four years steps are being taken in the Russian Federation to organize the spatial development of its territory. The distribution of the urban population of Russia by types of settlements has been analyzed. The main problems of the territorial organization of the population have been identified. The negative aspects of the spatial development of Russia have been noted and, in this regard, the goals, directions and mechanisms of the strategy of spatial development of the Russian Federation for the period up to 2025 have been considered.